Stakeholders' views around the concept and diagnosis of mild cognitive impairment and their understanding of dementia prevention: A qualitative study: Dementia care research (research projects; nonpharmacological) / Behavioral interventions. (7th December 2020) - Poppe, Michaela; Mansour, Hassan; Rapaport, Penny; Palomo, Marina; Burton, Alexandra; Morgan‐Trimmer, Sarah; Carter, Christine; Roche, Moise; Higgs, Paul; Walker, Zuzana; Aguirre, Elisa; Bass, Nicholas; et al.
Abstract: Background: Many people live with an awareness of mild cognitive changes and an associated dementia risk. Previous authors describe the uncertainties of this liminal state between cognitive health and dementia. The interface of this group with health services is growing, driven by early dementia diagnosis campaigns and research about the preventative potential of health promotion. This brings both preventative opportunities and risks of medicalisation, which have not previously been qualitatively explored from the perspectives of professionals, clients and their family members. We ask how services respond to people with memory concerns currently, and how future dementia prevention interventions for people with memory concerns should be structured. Method: We conducted qualitative interviews with 18 people aged 60+ with subjective or objective memory problems, six family members, 10 health and social care professionals and 11 third sector workers. Interviews were audio‐recorded, transcribed and analysed using an inductive thematic approach. Interviews were conducted as part of the APPLE‐Tree (Active Prevention in People at risk of dementia: Lifestyle, bEhaviour change and Technology to REducE cognitive and functional decline) programme, which is an international collaboration run in the UK. Result: Three main themes were identified: 1) acknowledging the liminal state, compounded by current, discordant health service responses, which medicalise memory concerns yet situate responsibilities for their management with patients and families; 2) challenges of enabling change in contexts of physical and cognitive frailty and social disengagement, and 3) building on existing values, cultures and routines to facilitate the process of implementing and maintaining behavioural and lifestyle changes. Conclusion: This study extends our understanding of the complex liminal position of people with memory concerns seeking help. Effective dementia prevention must empower individuals within challenging contexts and acknowledge their existing values. This cannot be realised within current memory service responses. Our findings further feed into a dementia prevention intervention which is currently being developed as part of the APPLE‐Tree programme.